Is the right to use trademarks mandated by the TRIPS Agreement? - Carlos María Correa (South Centre, 2016)
Accepting the notion that a positive right to use a trademark is implicitly recognized by the TRIPS Agreement would have systemic implications in the context of WTO. On the one hand, it would mean that the interpretative rules of the VCLT are replaced by expansive standards of interpretation and that the expressed will of the WTO members is ignored. On the other, it would mean that a public policy, including in the vital area of public health, could be overridden by an alleged private right to use an intellectual property right. If this were the case, for instance, a patent owner could not be prevented from using his patented invention even if damaging to the environment or public health. However, the TRIPS Agreement does not oblige WTO members to confer the right to use a trademark. Such a right would nullify the sovereign right to regulate - including to prohibit - the use of trademarks, a right that WTO members retained under the TRIPS Agreement. Sovereign States cannot be deemed to have given up their regulatory rights except to the extent that they have explicitly agreed to restrict them, as under Article 20 of the TRIPS Agreement. It is not conceivable that the drafters of the TRIPS Agreement agreed to create a right to use a trademark - non-existent under the Paris Convention - enforceable against the States without even mentioning it. If the drafters of the TRIPS Agreement intended to include an obligation to respect a right to use a trademark, this should have been made under Article 16, "Rights conferred".
Keywords: 300